2020
DOI: 10.1186/s13018-020-01996-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distal tibial tuberosity high tibial osteotomy on postoperative patellar height and patellofemoral joint degeneration

Abstract: Background Distal tibial tuberosity high tibial osteotomy (DTT-HTO) can prevent distalization of the tibial tuberosity and thus patellar infera. However, no studies on the clinical and radiological effects of DTT-HTO on the patellofemoral joint have been conducted. The purpose of the study was to evaluate the effect of DTT-HTO on patella height and patellofemoral joint congruity based on the severity of patellofemoral joint OA. Methods Twenty-nine patients (33 knees) who underwent DTT-HTO and second-look art… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…There are different opinions about the effect of HTO on patellar height, but a consensus has already been reached regarding whether high tibial osteotomy above the tibial tuberosity can affect patellar height [ 6 , 12 , 17 20 ]. This was confirmed by previous retrospective clinical studies of DTT-HTO conducted by our team [ 9 ]. Patellar height disorder can lead to cartilage degeneration of the patellofemoral joint, loss of function, knee pain, and recurrent patellofemoral dislocation.…”
Section: Introductionsupporting
confidence: 88%
“…There are different opinions about the effect of HTO on patellar height, but a consensus has already been reached regarding whether high tibial osteotomy above the tibial tuberosity can affect patellar height [ 6 , 12 , 17 20 ]. This was confirmed by previous retrospective clinical studies of DTT-HTO conducted by our team [ 9 ]. Patellar height disorder can lead to cartilage degeneration of the patellofemoral joint, loss of function, knee pain, and recurrent patellofemoral dislocation.…”
Section: Introductionsupporting
confidence: 88%
“…It was reported that a surgically induced decrease in patella height might result in anterior knee pain, patellofemoral arthrosis, and decreased range of motion 38 , 39 , 40 . Subsequent patellofemoral biomechanical modifications were also demonstrated in previous studies with the development of patella or trochlear OA in 41% of patients who underwent OWHTO 17 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Open‐wedge distal tibial tuberosity osteotomy has been drawing attention as a valuable surgical option for osteoarthritis with varus knee, especially for patients with patella infra or patellofemoral joint degeneration. 4 , 5 , 15 , 16 Its difference from OWHTO is the descending osteotomy at the tibial tuberosity. Concerning the abovementioned complications, if a lateral hinge fracture occurs, the compression lag screw should be inserted in the same direction as the locking screw, and the use of a lag screw in OWDTO requires careful postoperative rehabilitation and follow‐up.…”
Section: Discussionmentioning
confidence: 99%